Special current terminal adopting innovative composite material and preparation method thereof
By using a composite material of conductive copper alloy and silicon carbide or graphene in the current terminal, combined with an anti-oxidation coating, the deficiencies of traditional current terminals in conductivity, mechanical strength and corrosion resistance are solved, and higher durability is achieved. sex and stability.
Patent Information
- Application Number
- CN202411647379.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-24
AI Technical Summary
Existing current terminals are difficult to have both conductivity, mechanical strength and corrosion resistance, and cannot meet the stability and reliability requirements under harsh conditions such as high temperature, high humidity, and high salt spray.
The conductive copper alloy is used as the substrate material, combined with silicon carbide or graphene as an enhanced material, to form a composite structure through the thermal pressure molding process, and apply antioxidant coating on the surface to improve the overall performance of the terminal.
The excellent conductive performance of the current terminal is realized, the mechanical strength and corrosion resistance performance is improved, the durability and stability in the harsh environment is enhanced, and the system energy consumption is reduced.
Abstract
Description
Technical Field
[0001] The invention relates to the field of current terminals, and in particular to a special current terminal using an innovative composite material and a preparation method thereof. Background Art
[0002] Traditional current terminal technologies for electronic devices refer to those technologies that have long been widely used in various electronic devices to connect and transmit current. These technologies mainly include various plugs, sockets, wiring terminals and connectors, etc.; they play a vital role in electronic devices to ensure that current can be transmitted stably and safely.
[0003] With the development of the power industry, current terminals, as key components connecting power sources and loads, have a direct impact on the safety and reliability of the entire circuit through their performance. Traditional current terminals are mostly made of metal materials such as copper and aluminum. Although they have good conductivity, they have poor durability and stability in high temperature and corrosive environments, which limits their use in some high-end applications.
[0004] There are two main types of current terminals commonly found on the market: one is pure copper terminals, and the other is silver-plated copper alloy terminals. Pure copper terminals have good electrical conductivity, but are more expensive and have poor corrosion resistance. Although silver-plated copper alloy terminals have improved corrosion resistance, the silver layer is easily worn, resulting in increased contact resistance, which can easily cause failures during long-term operation. In addition, there are some terminals made of stainless steel, which, although they are strong and corrosion-resistant, have poor electrical conductivity and increase the energy consumption of the system.
[0005] Existing current terminals have difficulty in achieving conductivity, mechanical strength, corrosion resistance, etc., and cannot meet the increasingly stringent working environment requirements. Especially under harsh conditions such as high temperature, high humidity, and high salt spray, current terminals made of traditional materials often exhibit poor stability and reliability. Summary of the invention
[0006] In order to improve the corrosion resistance of a current terminal, the present application provides a special current terminal using an innovative composite material and a preparation method thereof.
[0007] In the first aspect, the present application provides a special current terminal using an innovative composite material, which adopts the following technical solution: A special current terminal using an innovative composite material comprises a matrix material and a reinforcing material; the matrix material comprises a conductive copper alloy, and the reinforcing material comprises one of silicon carbide and graphene.
[0008] By adopting the above technical scheme, the present application adopts a conductive copper alloy as the matrix material, ensuring the excellent conductive performance of the current terminal; the reinforcing material is one of silicon carbide and graphene, which can improve the mechanical strength and corrosion resistance of the current terminal. When the current passes through, the conductive copper alloy matrix ensures low resistance and reduces energy loss. Silicon carbide is evenly dispersed in the matrix material, enhancing the overall strength and wear resistance of the material; in harsh environments such as high temperature, high humidity, and high salt spray, the current terminal using innovative composite materials has higher durability and stability, effectively avoiding failures caused by corrosion of traditional materials. The combination of high conductive copper alloy matrix and nano-scale silicon carbide particles not only improves the mechanical strength of the material, but also maintains excellent conductive properties and reduces the energy consumption of the system.
[0009] Preferably, the silicon carbide is modified silicon carbide, and the preparation method of the modified silicon carbide is: 20-40 parts by weight of silicon carbide, 5-15 parts by weight of polyvinyl pyrrolidone, 10-20 parts by weight of polycarbosilane and 10-30 parts by weight of deionized water are uniformly mixed, 2-6 parts by weight of tetramethylammonium hydroxide are added for ball milling, the precipitate is dried after centrifugation, and the modified silicon carbide is obtained by grinding.
[0010] By adopting the above-mentioned technical scheme, the present application modifies silicon carbide, and polyvinyl pyrrolidone can improve the dispersion performance of silicon carbide, which helps to improve the conductivity of the current terminal. At the same time, in the process of modifying silicon carbide, various raw materials are fully ground so that polycarbosilane and polyvinyl pyrrolidone are evenly dispersed on the surface of silicon carbide, providing an effective isolation layer, which helps to improve the performance and corrosion resistance of the current terminal in a high temperature environment.
[0011] Preferably, the weight ratio of silicon carbide, polyvinyl pyrrolidone and polycarbosilane is (2.8-3.6):1:(1.2-1.4).
[0012] By adopting the above technical solution, when silicon carbide, polyvinyl pyrrolidone and polycarbosilane are in a specific weight ratio, the three work together to improve the dispersion performance and viscosity of silicon carbide, thereby improving the stability and mechanical properties of the terminal.
[0013] Preferably, the particle size of the silicon carbide is in the range of 50-100 nm.
[0014] By adopting the above technical solution and selecting silicon carbide within a suitable particle size range, the silicon carbide particles can be evenly dispersed in the matrix, thereby enhancing the overall strength and wear resistance of the material.
[0015] Preferably, an anti-oxidation coating is provided on the surface of the terminal, and the thickness of the anti-oxidation coating is 5-10 μm.
[0016] By adopting the above technical solution, the anti-oxidation coating can effectively isolate the current terminal from corrosion by external corrosive media, thereby extending the service life of the terminal.
[0017] Preferably, the anti-oxidation coating is made of Ni-Cr alloy.
[0018] By adopting the above technical solution, Ni-Cr alloy is selected for the anti-oxidation coating, which further prolongs the service life of the current terminal, reduces maintenance costs, and improves the overall reliability of the system.
[0019] Preferably, the polycarbosilane is modified polycarbosilane, and the preparation method of the modified polycarbosilane is: 20-40 parts by weight of polycarbosilane and 5-15 parts by weight of tetrahydrofuran are mixed, 10-30 parts by weight of acrylonitrile and 1-3 parts by weight of catalyst are added, mixed and stirred, and vacuum dried to obtain the modified polycarbosilane.
[0020] By adopting the above-mentioned technical scheme, the present application modifies polycarbosilane, acrylonitrile and polycarbosilane undergo a polymerization reaction, and the cyanide group in acrylonitrile is introduced into polycarbosilane, thereby significantly improving the thermal stability and corrosion resistance of silicon carbide, and helping to improve the performance stability of current terminals in harsh environments.
[0021] Preferably, the weight ratio of the polycarbosilane, tetrahydrofuran and acrylonitrile is (2.5-3.2):1:(2.4-2.7).
[0022] By adopting the above technical solution, when polycarbosilane, tetrahydrofuran and acrylonitrile are in a specific weight ratio, the three together can increase the material properties, conductivity, thermal stability, mechanical strength and electromagnetic wave absorption performance of the current terminal, thereby improving the overall performance and reliability of the current terminal.
[0023] In the second aspect, the present application provides a method for preparing a special current terminal using an innovative composite material, which adopts the following technical solution: A method for preparing a special current terminal using an innovative composite material comprises the following steps: hot pressing a matrix material and a reinforcing material to obtain a composite structure; treating the surface of the composite structure with an anti-oxidation coating to obtain a terminal; and setting standard interfaces at both ends of the terminal to obtain the special current terminal.
[0024] By adopting the above technical solution, the base material and the reinforcing material are tightly combined through a hot pressing process, which helps to form a stable composite structure, thereby improving the durability and stability of the current terminal and effectively avoiding failures caused by corrosion of traditional materials.
[0025] In summary, this application has the following beneficial technical effects: 1. This application uses a conductive copper alloy as the base material to ensure the excellent conductivity of the current terminal; the reinforcing material is one of silicon carbide and graphene, which can improve the mechanical strength and corrosion resistance of the current terminal. When current passes through, the conductive copper alloy matrix ensures low resistance and reduces energy loss. Silicon carbide is evenly dispersed in the matrix material, enhancing the overall strength and wear resistance of the material; in harsh environments such as high temperature, high humidity, and high salt spray, the current terminal using innovative composite materials has higher durability and stability, effectively avoiding failures caused by corrosion of traditional materials. The combination of high-conductivity copper alloy matrix and nano-scale silicon carbide particles not only improves the mechanical strength of the material, but also maintains excellent conductivity and reduces the energy consumption of the system.
[0026] 2. The present application modifies silicon carbide, and polyvinyl pyrrolidone can improve the dispersion performance of silicon carbide, which helps to improve the conductivity of the current terminal. At the same time, in the process of modifying silicon carbide, various raw materials are fully ground so that polycarbosilane and polyvinyl pyrrolidone are evenly dispersed on the surface of silicon carbide, providing an effective isolation layer, which helps to improve the performance and corrosion resistance of the current terminal in a high temperature environment.
[0027] 3. The present application modifies polycarbosilane, and acrylonitrile reacts with polycarbosilane to introduce the cyanide group in acrylonitrile into polycarbosilane, thereby significantly improving the thermal stability and corrosion resistance of silicon carbide, and helping to improve the performance stability of current terminals in harsh environments. DETAILED DESCRIPTION
[0028] The present application is further described in detail below with reference to the embodiments and comparative examples: Example
[0029] Example 1 A method for preparing a special current terminal using an innovative composite material comprises the following steps: The matrix material and the reinforcing material are mixed and stirred, and hot-pressed to form a stable composite structure; the surface of the composite structure is treated with an anti-oxidation coating to obtain a terminal; standard interfaces are set at both ends of the terminal to facilitate connection with other electrical components to obtain a special current terminal.
[0030] During operation, first check whether the terminal appearance is damaged or deformed, then clean the terminal surface to remove oil and impurities, then connect the terminal to the circuit to ensure that the connection is firm and reliable, and finally check the terminal connection status regularly and deal with any abnormalities in a timely manner.
[0031] The base material is a conductive copper alloy, CuAg0.15 (copper content 99.85%, silver content 0.15%), with a conductivity of 100% IACS, which reduces energy loss and ensures low resistance when current passes through; the reinforcing material is silicon carbide with a particle size of 50nm; the material of the anti-oxidation coating is Ni-Cr alloy, and the coating thickness is 5μm.
[0032] Example 2 The matrix material and the reinforcing material are mixed and stirred, and hot-pressed to form a stable composite structure; the surface of the composite structure is treated with an anti-oxidation coating to obtain a terminal; standard interfaces are set at both ends of the terminal to facilitate connection with other electrical components to obtain a special current terminal.
[0033] During operation, first check whether the terminal appearance is damaged or deformed, then clean the terminal surface to remove oil and impurities, then connect the terminal to the circuit to ensure that the connection is firm and reliable, and finally check the terminal connection status regularly and deal with any abnormalities in a timely manner.
[0034] The matrix material is a conductive copper alloy, CuAg0.15 (copper content 99.85%, silver content 0.15%), with a conductivity of 100% IACS, which reduces energy loss and ensures low resistance when current passes through; the reinforcing material is graphene, the particle size of graphene is 50nm, the material of the anti-oxidation coating is Ni-Cr alloy, and the thickness of the coating is 5μm.
[0035] Example 3 A method for preparing a special current terminal using an innovative composite material comprises the following steps: The matrix material and the reinforcing material are mixed and stirred, and hot-pressed to form a stable composite structure; the surface of the composite structure is treated with an anti-oxidation coating to obtain a terminal; standard interfaces are set at both ends of the terminal to facilitate connection with other electrical components to obtain a special current terminal.
[0036] During operation, first check whether the terminal appearance is damaged or deformed, then clean the terminal surface to remove oil and impurities, then connect the terminal to the circuit to ensure that the connection is firm and reliable, and finally check the terminal connection status regularly and deal with any abnormalities in a timely manner.
[0037] The base material is a conductive copper alloy, CuAg0.15 (copper content 99.85%, silver content 0.15%), with a conductivity of 100% IACS, which reduces energy loss and ensures low resistance when current passes through; the reinforcing material is modified silicon carbide with a particle size of 50nm; the material of the anti-oxidation coating is Ni-Cr alloy, and the coating thickness is 5μm.
[0038] The preparation method of modified silicon carbide is as follows: 20g silicon carbide, 5g polyvinyl pyrrolidone, 10g polycarbosilane and 10g deionized water are mixed evenly at a temperature of 60°C for 30 minutes, 2g tetramethylammonium hydroxide is added and transferred to a ball mill for 2 hours, and after grinding, the mixture is transferred to a centrifuge for centrifugation, and the precipitate is transferred to an oven and dried at a temperature of 100°C for 2 hours, and the grinding is continued for 5 minutes to obtain modified silicon carbide.
[0039] The polyvinyl pyrrolidone is from Shandong Dengnuo New Material Technology Co., Ltd., model HS963, item number HS-748; the polycarbosilane is specifically polycarbomethylsilane (MW=1400).
[0040] Example 4 A method for preparing a special current terminal using an innovative composite material comprises the following steps: The matrix material and the reinforcing material are mixed and stirred, and hot-pressed to form a stable composite structure; the surface of the composite structure is treated with an anti-oxidation coating to obtain a terminal; standard interfaces are set at both ends of the terminal to facilitate connection with other electrical components to obtain a special current terminal.
[0041] During operation, first check whether the terminal appearance is damaged or deformed, then clean the terminal surface to remove oil and impurities, then connect the terminal to the circuit to ensure that the connection is firm and reliable, and finally check the terminal connection status regularly and deal with any abnormalities in a timely manner.
[0042] The base material is a conductive copper alloy, CuAg0.15 (copper content 99.85%, silver content 0.15%), with a conductivity of 100% IACS, which reduces energy loss and ensures low resistance when current passes through; the reinforcing material is modified silicon carbide with a particle size of 50nm; the material of the anti-oxidation coating is Ni-Cr alloy, and the coating thickness is 5μm.
[0043] The preparation method of modified silicon carbide is as follows: 40g of silicon carbide, 15g of polyvinyl pyrrolidone, 20g of polycarbosilane and 30g of deionized water are mixed evenly at a temperature of 60°C for 30 minutes, 6g of tetramethylammonium hydroxide is added and transferred to a ball mill for 2 hours, and after grinding, the mixture is transferred to a centrifuge for centrifugation, and the precipitate is transferred to an oven and dried at a temperature of 100°C for 2 hours, and the grinding is continued for 5 minutes to obtain modified silicon carbide.
[0044] The polyvinyl pyrrolidone is from Shandong Dengnuo New Material Technology Co., Ltd., model HS963, item number HS-748; the polycarbosilane is specifically polycarbomethylsilane (MW=1400).
[0045] Example 5 A method for preparing a special current terminal using an innovative composite material comprises the following steps: The matrix material and the reinforcing material are mixed and stirred, and hot-pressed to form a stable composite structure; the surface of the composite structure is treated with an anti-oxidation coating to obtain a terminal; standard interfaces are set at both ends of the terminal to facilitate connection with other electrical components to obtain a special current terminal.
[0046] During operation, first check whether the terminal appearance is damaged or deformed, then clean the terminal surface to remove oil and impurities, then connect the terminal to the circuit to ensure that the connection is firm and reliable, and finally check the terminal connection status regularly and deal with any abnormalities in a timely manner.
[0047] The base material is a conductive copper alloy, CuAg0.15 (copper content 99.85%, silver content 0.15%), with a conductivity of 100% IACS, which reduces energy loss and ensures low resistance when current passes through; the reinforcing material is modified silicon carbide with a particle size of 50nm; the material of the anti-oxidation coating is Ni-Cr alloy, and the coating thickness is 5μm.
[0048] The preparation method of modified silicon carbide is as follows: 28g of silicon carbide, 10g of polyvinyl pyrrolidone, 12g of polycarbosilane and 30g of deionized water are mixed evenly at a temperature of 60°C for 30 minutes, 6g of tetramethylammonium hydroxide is added and transferred to a ball mill for 2 hours, and after grinding, the mixture is transferred to a centrifuge for centrifugation, and the precipitate is transferred to an oven and dried at a temperature of 100°C for 2 hours, and the grinding is continued for 5 minutes to obtain modified silicon carbide.
[0049] The polyvinyl pyrrolidone is from Shandong Dengnuo New Material Technology Co., Ltd., model HS963, item number HS-748; the polycarbosilane is specifically polycarbomethylsilane (MW=1400).
[0050] Example 6 A method for preparing a special current terminal using an innovative composite material comprises the following steps: The matrix material and the reinforcing material are mixed and stirred, and hot-pressed to form a stable composite structure; the surface of the composite structure is treated with an anti-oxidation coating to obtain a terminal; standard interfaces are set at both ends of the terminal to facilitate connection with other electrical components to obtain a special current terminal.
[0051] During operation, first check whether the terminal appearance is damaged or deformed, then clean the terminal surface to remove oil and impurities, then connect the terminal to the circuit to ensure that the connection is firm and reliable, and finally check the terminal connection status regularly and deal with any abnormalities in a timely manner.
[0052] The base material is a conductive copper alloy, CuAg0.15 (copper content 99.85%, silver content 0.15%), with a conductivity of 100% IACS, which reduces energy loss and ensures low resistance when current passes through; the reinforcing material is modified silicon carbide with a particle size of 50nm; the material of the anti-oxidation coating is Ni-Cr alloy, and the coating thickness is 5μm.
[0053] The preparation method of modified silicon carbide is as follows: 36g of silicon carbide, 10g of polyvinyl pyrrolidone, 14g of polycarbosilane and 30g of deionized water are mixed evenly at a temperature of 60°C for 30 minutes, 6g of tetramethylammonium hydroxide is added and transferred to a ball mill for 2 hours, and after grinding, the mixture is transferred to a centrifuge for centrifugation, and the precipitate is transferred to an oven and dried at a temperature of 100°C for 2 hours, and the grinding is continued for 5 minutes to obtain modified silicon carbide.
[0054] The polyvinyl pyrrolidone is from Shandong Dengnuo New Material Technology Co., Ltd., model HS963, item number HS-748; the polycarbosilane is specifically polycarbomethylsilane (MW=1400).
[0055] Example 7 A method for preparing a special current terminal using an innovative composite material comprises the following steps: The matrix material and the reinforcing material are mixed and stirred, and hot-pressed to form a stable composite structure; the surface of the composite structure is treated with an anti-oxidation coating to obtain a terminal; standard interfaces are set at both ends of the terminal to facilitate connection with other electrical components to obtain a special current terminal.
[0056] During operation, first check whether the terminal appearance is damaged or deformed, then clean the terminal surface to remove oil and impurities, then connect the terminal to the circuit to ensure that the connection is firm and reliable, and finally check the terminal connection status regularly and deal with any abnormalities in a timely manner.
[0057] The base material is a conductive copper alloy, CuAg0.15 (copper content 99.85%, silver content 0.15%), with a conductivity of 100% IACS, which reduces energy loss and ensures low resistance when current passes through; the reinforcing material is modified silicon carbide with a particle size of 50nm; the material of the anti-oxidation coating is Ni-Cr alloy, and the coating thickness is 5μm.
[0058] The preparation method of modified silicon carbide is as follows: 36g of silicon carbide, 10g of polyvinyl pyrrolidone, 14g of modified polycarbosilane and 30g of deionized water are mixed evenly at a temperature of 60°C for 30 minutes, 6g of tetramethylammonium hydroxide is added and transferred to a ball mill for 2 hours, and after grinding, the mixture is transferred to a centrifuge for centrifugation, and the precipitate is transferred to an oven and dried at a temperature of 100°C for 2 hours, and the grinding is continued for 5 minutes to obtain modified silicon carbide.
[0059] The polyvinyl pyrrolidone is from Shandong Dengnuo New Material Technology Co., Ltd., model HS963, item number HS-748; the polycarbosilane is specifically polycarbomethylsilane (MW=1400).
[0060] The preparation method of modified polycarbosilane is as follows: 20g polycarbosilane and 5g tetrahydrofuran are mixed at a temperature of 50°C for 10min, 10g acrylonitrile and 1g catalyst are added, mixed and stirred for 30min, and then transferred to vacuum drying to obtain modified polycarbosilane. The catalyst is chloroplatinic acid-amine catalyst.
[0061] Example 8 A method for preparing a special current terminal using an innovative composite material comprises the following steps: The matrix material and the reinforcing material are mixed and stirred, and hot-pressed to form a stable composite structure; the surface of the composite structure is treated with an anti-oxidation coating to obtain a terminal; standard interfaces are set at both ends of the terminal to facilitate connection with other electrical components to obtain a special current terminal.
[0062] During operation, first check whether the terminal appearance is damaged or deformed, then clean the terminal surface to remove oil and impurities, then connect the terminal to the circuit to ensure that the connection is firm and reliable, and finally check the terminal connection status regularly and deal with any abnormalities in a timely manner.
[0063] The base material is a conductive copper alloy, CuAg0.15 (copper content 99.85%, silver content 0.15%), with a conductivity of 100% IACS, which reduces energy loss and ensures low resistance when current passes through; the reinforcing material is modified silicon carbide with a particle size of 50nm; the material of the anti-oxidation coating is Ni-Cr alloy, and the coating thickness is 5μm.
[0064] The preparation method of modified silicon carbide is as follows: 36g of silicon carbide, 10g of polyvinyl pyrrolidone, 14g of modified polycarbosilane and 30g of deionized water are mixed evenly at a temperature of 60°C for 30 minutes, 6g of tetramethylammonium hydroxide is added and transferred to a ball mill for 2 hours, and after grinding, the mixture is transferred to a centrifuge for centrifugation, and the precipitate is transferred to an oven and dried at a temperature of 100°C for 2 hours, and the grinding is continued for 5 minutes to obtain modified silicon carbide.
[0065] The polyvinyl pyrrolidone is from Shandong Dengnuo New Material Technology Co., Ltd., model HS963, item number HS-748; the polycarbosilane is specifically polycarbomethylsilane (MW=1400).
[0066] The preparation method of modified polycarbosilane is as follows: 20g polycarbosilane and 5g tetrahydrofuran are mixed at a temperature of 50°C for 10min, 10g acrylonitrile and 1g catalyst are added, mixed and stirred for 30min, and then transferred to vacuum drying to obtain modified polycarbosilane. The catalyst is chloroplatinic acid-amine catalyst.
[0067] Example 9 A method for preparing a special current terminal using an innovative composite material comprises the following steps: The matrix material and the reinforcing material are mixed and stirred, and hot-pressed to form a stable composite structure; the surface of the composite structure is treated with an anti-oxidation coating to obtain a terminal; standard interfaces are set at both ends of the terminal to facilitate connection with other electrical components to obtain a special current terminal.
[0068] During operation, first check whether the terminal appearance is damaged or deformed, then clean the terminal surface to remove oil and impurities, then connect the terminal to the circuit to ensure that the connection is firm and reliable, and finally check the terminal connection status regularly and deal with any abnormalities in a timely manner.
[0069] The base material is a conductive copper alloy, CuAg0.15 (copper content 99.85%, silver content 0.15%), with a conductivity of 100% IACS, which reduces energy loss and ensures low resistance when current passes through; the reinforcing material is modified silicon carbide with a particle size of 50nm; the material of the anti-oxidation coating is Ni-Cr alloy, and the coating thickness is 5μm.
[0070] The preparation method of modified silicon carbide is as follows: 36g of silicon carbide, 10g of polyvinyl pyrrolidone, 14g of modified polycarbosilane and 30g of deionized water are mixed evenly at a temperature of 60°C for 30 minutes, 6g of tetramethylammonium hydroxide is added and transferred to a ball mill for 2 hours, and after grinding, the mixture is transferred to a centrifuge for centrifugation, and the precipitate is transferred to an oven and dried at a temperature of 100°C for 2 hours, and the grinding is continued for 5 minutes to obtain modified silicon carbide.
[0071] The polyvinyl pyrrolidone is from Shandong Dengnuo New Material Technology Co., Ltd., model HS963, item number HS-748; the polycarbosilane is specifically polycarbomethylsilane (MW=1400).
[0072] The preparation method of modified polycarbosilane is as follows: 25g polycarbosilane and 10g tetrahydrofuran are mixed at a temperature of 50°C for 10 minutes, 24g acrylonitrile and 1g catalyst are added, mixed and stirred for 30 minutes, and then transferred to vacuum drying to obtain modified polycarbosilane. The catalyst is chloroplatinic acid-amine catalyst.
[0073] Example 10 A method for preparing a special current terminal using an innovative composite material comprises the following steps: The matrix material and the reinforcing material are mixed and stirred, and hot-pressed to form a stable composite structure; the surface of the composite structure is treated with an anti-oxidation coating to obtain a terminal; standard interfaces are set at both ends of the terminal to facilitate connection with other electrical components to obtain a special current terminal.
[0074] During operation, first check whether the terminal appearance is damaged or deformed, then clean the terminal surface to remove oil and impurities, then connect the terminal to the circuit to ensure that the connection is firm and reliable, and finally check the terminal connection status regularly and deal with any abnormalities in a timely manner.
[0075] The base material is a conductive copper alloy, CuAg0.15 (copper content 99.85%, silver content 0.15%), with a conductivity of 100% IACS, which reduces energy loss and ensures low resistance when current passes through; the reinforcing material is modified silicon carbide with a particle size of 50nm; the material of the anti-oxidation coating is Ni-Cr alloy, and the coating thickness is 5μm.
[0076] The preparation method of modified silicon carbide is as follows: 36g of silicon carbide, 10g of polyvinyl pyrrolidone, 14g of modified polycarbosilane and 30g of deionized water are mixed evenly at a temperature of 60°C for 30 minutes, 6g of tetramethylammonium hydroxide is added and transferred to a ball mill for 2 hours, and after grinding, the mixture is transferred to a centrifuge for centrifugation, and the precipitate is transferred to an oven and dried at a temperature of 100°C for 2 hours, and the grinding is continued for 5 minutes to obtain modified silicon carbide.
[0077] The polyvinyl pyrrolidone is from Shandong Dengnuo New Material Technology Co., Ltd., model HS963, item number HS-748; the polycarbosilane is specifically polycarbomethylsilane (MW=1400).
[0078] The preparation method of modified polycarbosilane is as follows: 32g polycarbosilane and 10g tetrahydrofuran are mixed at a temperature of 50°C for 10min, 27g acrylonitrile and 1g catalyst are added, mixed and stirred for 30min, and then transferred to vacuum drying to obtain modified polycarbosilane. The catalyst is chloroplatinic acid-amine catalyst.
[0079] Comparative Example Comparative Example 1 A method for preparing a special current terminal using an innovative composite material comprises the following steps: The matrix material and the reinforcing material are mixed and stirred, and hot-pressed to form a stable composite structure; the surface of the composite structure is treated with an anti-oxidation coating to obtain a terminal; standard interfaces are set at both ends of the terminal to facilitate connection with other electrical components to obtain a special current terminal.
[0080] During operation, first check whether the terminal appearance is damaged or deformed, then clean the terminal surface to remove oil and impurities, then connect the terminal to the circuit to ensure that the connection is firm and reliable, and finally check the terminal connection status regularly and deal with any abnormalities in a timely manner.
[0081] The base material is a conductive copper alloy, CuAg0.15 (copper content 99.85%, silver content 0.15%), with a conductivity of 100% IACS, which reduces energy loss and ensures low resistance when current passes through; the reinforcing material is a high-conductivity copper alloy, the material of the anti-oxidation coating is Ni-Cr alloy, and the thickness of the coating is 5μm.
[0082] Comparative Example 2 A method for preparing a special current terminal using an innovative composite material comprises the following steps: The matrix material and the reinforcing material are mixed and stirred, and hot-pressed to form a stable composite structure; the surface of the composite structure is treated with an anti-oxidation coating to obtain a terminal; standard interfaces are set at both ends of the terminal to facilitate connection with other electrical components to obtain a special current terminal.
[0083] During operation, first check whether the terminal appearance is damaged or deformed, then clean the terminal surface to remove oil and impurities, then connect the terminal to the circuit to ensure that the connection is firm and reliable, and finally check the terminal connection status regularly and deal with any abnormalities in a timely manner.
[0084] The base material is a conductive copper alloy, CuAg0.15 (copper content 99.85%, silver content 0.15%), with a conductivity of 100% IACS, which reduces energy loss and ensures low resistance when current passes through; the reinforcing material is stainless steel with a particle size of 50nm; the material of the anti-oxidation coating is Ni-Cr alloy, and the coating thickness is 5μm.
[0085] Comparative Example 3 A method for preparing a special current terminal using an innovative composite material comprises the following steps: The matrix material and the reinforcing material are mixed and stirred, and hot-pressed to form a stable composite structure; the surface of the composite structure is treated with an anti-oxidation coating to obtain a terminal; standard interfaces are set at both ends of the terminal to facilitate connection with other electrical components to obtain a special current terminal.
[0086] During operation, first check whether the terminal appearance is damaged or deformed, then clean the terminal surface to remove oil and impurities, then connect the terminal to the circuit to ensure that the connection is firm and reliable, and finally check the terminal connection status regularly and deal with any abnormalities in a timely manner.
[0087] The matrix material is a conductive copper alloy, CuAg0.15 (copper content 99.85%, silver content 0.15%), with a conductivity of 100% IACS, which reduces energy loss and ensures low resistance when current passes through; the reinforcing material is nano-titanium dioxide, the particle size of nano-titanium dioxide is 50nm, the material of the anti-oxidation coating is Ni-Cr alloy, and the thickness of the coating is 5μm.
[0088] Performance testing: Corrosive environment exposure test: After the special current terminal is immersed in a 5% sodium chloride aqueous solution at 23°C for 24 hours, it is placed in a high temperature and high humidity environment of 85°C and 85% RH for 24 hours. Then, the contact resistance of the terminal is measured by the four-terminal method. The current value is set to 10mA.
[0089] Tensile strength test: The tensile strength of the special current terminals prepared in Examples 1-10 and Comparative Examples 1-3 was tested according to UL486A-1991JIS. Corrosive environment placement (mΩ) Tensile strength MPa Example 1 5.4 213 Example 2 5.3 211 Example 3 4.5 226 Example 4 4.3 227 Example 5 4.3 233 Example 6 4.2 235 Example 7 2.6 248 Example 8 2.5 250 Example 9 1.1 263 Example 10 1.2 265 Comparative Example 1 7.8 165 Comparative Example 2 5.8 161 Comparative Example 3 8.6 188
[0090] According to the data comparison of Examples 1-2 and Comparative Examples 1-3, the present application adopts a conductive copper alloy as the matrix material, which ensures the excellent conductivity of the current terminal; the reinforcing material is one of silicon carbide and graphene, which can improve the mechanical strength and corrosion resistance of the current terminal. When the current passes through, the conductive copper alloy matrix ensures low resistance and reduces energy loss. Silicon carbide is evenly dispersed in the matrix material, which enhances the overall strength and wear resistance of the material; in harsh environments such as high temperature, high humidity, and high salt spray, the current terminal using innovative composite materials has higher durability and stability, effectively avoiding failures caused by corrosion of traditional materials. The combination of high conductive copper alloy matrix and nano-scale silicon carbide particles not only improves the mechanical strength of the material, but also maintains excellent conductivity and reduces the energy consumption of the system.
[0091] According to the data comparison between Example 1 and Examples 3-4, the present application modifies silicon carbide, and polyvinyl pyrrolidone can improve the dispersion performance of silicon carbide, which helps to improve the conductivity of the current terminal. At the same time, in the process of modifying silicon carbide, various raw materials are fully ground so that polycarbosilane and polyvinyl pyrrolidone are evenly dispersed on the surface of silicon carbide, providing an effective isolation layer, which helps to improve the performance and corrosion resistance of the current terminal in a high temperature environment.
[0092] According to the data comparison of Examples 4-6, when silicon carbide, polyvinyl pyrrolidone and polycarbosilane are in a specific weight ratio, the three work together to improve the dispersion performance and viscosity of silicon carbide, thereby improving the stability and mechanical properties of the terminal.
[0093] According to the data comparison of Examples 6-8, the present application modifies polycarbosilane, acrylonitrile and polycarbosilane undergo a polymerization reaction, and the cyanide group in acrylonitrile is introduced into the polycarbosilane, thereby significantly improving the thermal stability and corrosion resistance of silicon carbide, and helping to improve the performance stability of the current terminal in harsh environments.
[0094] According to the data comparison of Examples 8-10, when polycarbosilane, tetrahydrofuran and acrylonitrile are in a specific weight ratio, the three together can increase the material properties, conductivity, thermal stability, mechanical strength and electromagnetic wave absorption performance of the current terminal, thereby improving the overall performance and reliability of the current terminal.
[0095] The specific embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A special current terminal using an innovative composite material, characterized in that: It comprises a base material and a reinforcing material; the base material comprises a conductive copper alloy, and the reinforcing material comprises one of silicon carbide and graphene.
2. The special current terminal using the innovative composite material according to claim 1, characterized in that: The silicon carbide is modified silicon carbide. The preparation method of the modified silicon carbide is: 20-40 parts by weight of silicon carbide, 5-15 parts by weight of polyvinyl pyrrolidone, 10-20 parts by weight of polycarbosilane and 10-30 parts by weight of deionized water are uniformly mixed, 2-6 parts by weight of tetramethylammonium hydroxide are added for ball milling, the precipitate is dried after centrifugation, and the modified silicon carbide is obtained by grinding.
3. The special current terminal using the innovative composite material according to claim 1, characterized in that: The weight ratio of silicon carbide, polyvinyl pyrrolidone and polycarbosilane is (2.8-3.6):1:(1.2-1.4).
4. The special current terminal using the innovative composite material according to claim 1, characterized in that: The particle size of the silicon carbide is in the range of 50-100 nm.
5. The special current terminal using the innovative composite material according to claim 1, characterized in that: The terminal surface is provided with an anti-oxidation coating, and the thickness of the anti-oxidation coating is 5-10 μm.
6. The special current terminal using the innovative composite material according to claim 1, characterized in that: The anti-oxidation coating is made of Ni-Cr alloy.
7. The special current terminal using the innovative composite material according to claim 1, characterized in that: The polycarbosilane is modified polycarbosilane, and the preparation method of the modified polycarbosilane is as follows: 20-40 parts by weight of polycarbosilane and 5-15 parts by weight of tetrahydrofuran are mixed, 10-30 parts by weight of acrylonitrile and 1-3 parts by weight of catalyst are added, mixed and stirred, and vacuum dried to obtain the modified polycarbosilane.
8. The special current terminal using the innovative composite material according to claim 1, characterized in that: The weight ratio of the polycarbosilane, tetrahydrofuran and acrylonitrile is (2.5-3.2):1:(2.4-2.7).
9. A method for preparing a special current terminal using an innovative composite material, comprising the steps of: The base material and the reinforcing material are hot-pressed to obtain a composite structure; an anti-oxidation coating is applied to the surface of the composite structure to obtain a terminal; Standard interfaces are arranged at both ends of the terminal to obtain the special current terminal.